1999
DOI: 10.1046/j.1365-2842.1999.00379.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of an oral prosthesis on the quality of life for head and neck cancer patients

Abstract: The quality of life (QOL) in patients with cancer in the head and neck regions has become an increasingly important factor in medical treatment. We examined the effect of a prosthesis on the QOL based on the patients' own subjective evaluations. Sixty-eight head and neck cancer patients who had been treated in the Department of Prosthetic Dentistry of the Faculty of Dentistry, Kyushu University, were compared with 35 denture wearers as a control. General denture satisfaction in the control group showed a stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 11 publications
1
17
0
2
Order By: Relevance
“…The elastic modulus of the rDMP1-mediated crystalline HAP was found to be 6.58 Ϯ 1.02 GPa, whereas the elastic modulus of platy HAP crystals grown in the presence of type I collagen and rDMP1 was found to be 18.08 Ϯ 1.28 GPa. These values are comparable with the elastic moduli reported (32)(33)(34)(35) for various types of bone and dentine (Fig. 9c).…”
Section: Crystallinity Of Hap Mediated By Native and Recombinant Dmp1-supporting
confidence: 91%
“…The elastic modulus of the rDMP1-mediated crystalline HAP was found to be 6.58 Ϯ 1.02 GPa, whereas the elastic modulus of platy HAP crystals grown in the presence of type I collagen and rDMP1 was found to be 18.08 Ϯ 1.28 GPa. These values are comparable with the elastic moduli reported (32)(33)(34)(35) for various types of bone and dentine (Fig. 9c).…”
Section: Crystallinity Of Hap Mediated By Native and Recombinant Dmp1-supporting
confidence: 91%
“…If this is the case, teeth and dentures may become increasingly important in terms of their impact on OHRQoL. In a group of patients suffering from head and neck cancer, who did not have to undergo RT, it has been shown that dentures had a positive influence on OHRQoL particularly if a serious illness was present [34].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that in both a cancer group wearing maxillofacial prostheses, as well as in a control group wearing conventional dentures, females rated most variables lower than the males. 15 However, the authors failed to find significant differences, most probably because the sample size was small. In another study, it was found that males could adapt more easily to new removable partial dentures than females.…”
Section: Sex Differences-conventional Denturesmentioning
confidence: 98%